The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jctb.5519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluorescent dyes to measure protein aggregation within mammalian cell culture supernatants

Abstract: BACKGROUNDA current challenge in bioprocessing is the ability to analyse critical quality attributes such as aggregation without prior purification. This study evaluated the use of fluorescent dyes (Bis‐ANS, SYPRO Orange, Thioflavin T and ProteoStat) to characterise mAb aggregates in Chinese hamster ovary clarified cultures.RESULTSThe null and mAb culture supernatants showed an increase in fluorescence intensity over the duration of the culture. The null cultures on day 14 saw a rapid increase in fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…A recent study with an early prototype Thioflavin T revealed that the dye exhibits a 6‐fold higher affinity towards BSA dimers than monomers . Conversely, there is also evidence to suggest that the dye can bind to specific parts of monomers, non‐ β ‐sheet cavities, and therefore fails to distinguish between different protein conformations …”
Section: Resultsmentioning
confidence: 99%
“…A recent study with an early prototype Thioflavin T revealed that the dye exhibits a 6‐fold higher affinity towards BSA dimers than monomers . Conversely, there is also evidence to suggest that the dye can bind to specific parts of monomers, non‐ β ‐sheet cavities, and therefore fails to distinguish between different protein conformations …”
Section: Resultsmentioning
confidence: 99%
“…This would make it easier to assess the variations if the sample structure that may be induced during synthesis. Protein aggregation can be measured by evaluating the fluorescence spectra of the NBC [77]. Moreover, the mechanisms involved in photoactivated NBC cell death leading to free radical apoptosis of CSCs remain unknown, as cell death may be caused by distinct, but overlapping, signaling pathways that respond to different stimuli [78].…”
Section: Discussionmentioning
confidence: 99%
“…Two microliters of ProteoStat® Fluorescent Dye (Enzo Life Sciences, USA) was added to each test sample containing 200 μg/ml of IgG in a 96-well black, clear flat-bottomed plate (Greiner Bio-One, Austria). This dye is widely used to detect protein aggregates (27) and is benchmarked with IgG by the manufacturer (28). The microplate containing test samples was incubated in the dark for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%